2007
DOI: 10.1093/jn/137.1.175s
|View full text |Cite
|
Sign up to set email alerts
|

Why Do African Americans Get More Colon Cancer than Native Africans?

Abstract: The incidence of colorectal cancer (CRC) is dramatically higher in African Americans (AAs) than in Native Africans (NAs) (60:100,000 vs. <1:100,000) and slightly higher than in Caucasian Americans (CAs). To explore whether the difference could be explained by interactions between diet and colonic bacterial flora, we compared randomly selected samples of healthy 50- to 65-y-old AAs (n = 17) with NAs (n = 18) and CAs (n = 17). Diet was measured by 3-d recall, and colonic metabolism by breath hydrogen and methane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
145
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(151 citation statements)
references
References 37 publications
4
145
0
2
Order By: Relevance
“…In sharp contrast, rural Africans rarely get the disease (3). Studies of ours have ascribed this difference to higher meat and fat intakes in Americans and to higher resistant starch intakes in Africans (4).…”
Section: Introductionmentioning
confidence: 65%
“…In sharp contrast, rural Africans rarely get the disease (3). Studies of ours have ascribed this difference to higher meat and fat intakes in Americans and to higher resistant starch intakes in Africans (4).…”
Section: Introductionmentioning
confidence: 65%
“…Fiber consumption is significantly associated with 50%-60% reduced risk of colorectal cancer in African Americans and non-significantly with 30% reduced risk of colorectal cancer in Whites [56] . Hydrogen response to 10 g of oral lactulose is significantly higher in the African-American than in the Caucasian American population implicating a difference in colonic bacterial metabolism between the two groups [57] . African Americans in all age groups seem to consume fewer mean daily servings of total dairy, milk, cheese, and yogurt than non-African Americans, and have lower mean intakes of calcium, magnesium, and phosphorus [58] .…”
Section: Racial Variation Of Colorectal Cancer Riskmentioning
confidence: 97%
“…Only a small number of studies have compared the gut microbiome composition of CRC patients from different populations. A study comparing the microbiome of healthy individuals from a high CRC risk population (African-Americans) with a low risk population (Africans) 36,37 showed differences in the microbiome composition between the 2 populations, which probably reflect a diet high in fiber and less meat and fat for Africans compared to the African-American diet more comparable to the Western diet. The study found an over abundance of Prevotella, Succinivibrio, and Oscillospira in Africans and a predominance of the genus Bacteroides in African-Americans.…”
Section: Introductionmentioning
confidence: 99%